2010
DOI: 10.1016/j.bpj.2010.05.031
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility of Bicoid Captured by Fluorescence Correlation Spectroscopy: Implication for the Rapid Establishment of Its Gradient

Abstract: The Bicoid (Bcd) morphogen is essential for pattern formation in fruit flies. It forms an exponential concentration gradient along the embryo AP axis and turns on cascades of target genes in distinct anterior domains. The most commonly accepted model for gradient formation assumes that Bcd travels by simple diffusion and is uniformly degraded across syncytial embryos, yet several recent studies have challenged these ideas. Here, the question of Bcd mobility was investigated using fluorescence correlation spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
147
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(169 citation statements)
references
References 20 publications
19
147
0
Order By: Relevance
“…The morphogens Dpp and Wingless (Wg) have relatively short ranges in the Drosophila wing disc (Entchev et al, 2000;Teleman and Cohen, 2000;Kicheva et al, 2007;Bollenbach et al, 2008), Bicoid (Bcd) has a mid-range in Drosophila embryos (Driever and Nüsslein-Volhard, 1988a;Driever and Nüsslein-Volhard, 1988b;Gregor et al, 2007;Abu-Arish et al, 2010;Castle et al, 2011;Drocco et al, 2011), and Nodal and FGF8 can act over longer distances in zebrafish embryos (Gritsman et al, 2000;Chen and Schier, 2001;Harvey and Smith, 2009;Yu et al, 2009;Müller et al, 2012). Intriguingly, Lefty has a much longer range than Nodal, even though both molecules are TGFβ superfamily members and expressed in zebrafish embryos.…”
Section: Box 8 Signaling Rangementioning
confidence: 99%
See 1 more Smart Citation
“…The morphogens Dpp and Wingless (Wg) have relatively short ranges in the Drosophila wing disc (Entchev et al, 2000;Teleman and Cohen, 2000;Kicheva et al, 2007;Bollenbach et al, 2008), Bicoid (Bcd) has a mid-range in Drosophila embryos (Driever and Nüsslein-Volhard, 1988a;Driever and Nüsslein-Volhard, 1988b;Gregor et al, 2007;Abu-Arish et al, 2010;Castle et al, 2011;Drocco et al, 2011), and Nodal and FGF8 can act over longer distances in zebrafish embryos (Gritsman et al, 2000;Chen and Schier, 2001;Harvey and Smith, 2009;Yu et al, 2009;Müller et al, 2012). Intriguingly, Lefty has a much longer range than Nodal, even though both molecules are TGFβ superfamily members and expressed in zebrafish embryos.…”
Section: Box 8 Signaling Rangementioning
confidence: 99%
“…Low values indicate a short range, whereas large values indicate a long range. For comparison, the absolute range λ= ͱ D/k --is shown in B. λ and 1/φ were calculated from literature values of D and k (Gregor et al, 2007;Kicheva et al, 2007;Yu et al, 2009;Abu-Arish et al, 2010;Castle et al, 2011;Drocco et al, 2011;Wartlick et al, 2011;Müller et al, 2012;Zhou et al, 2012). (Teleman and Cohen, 2000).…”
Section: Box 8 Signaling Rangementioning
confidence: 99%
“…In biological systems, however, and in particular in cells, diffusive motions are often found to deviate from simple Fickian diffusion 1 . This deviation can take dif-ferent forms, from an apparent size-dependent viscosity of the medium to a non-Gaussian distribution of displacements or to a mean-squared displacement that is not directly proportional to time [2][3][4][5][6][7][8][9][10][11][12][13] . Similar effects can be recreated in vitro, using for example polymer solutions [14][15][16] , gels [17][18][19][20] or colloidal suspensions 21 .…”
Section: Introductionmentioning
confidence: 99%
“…3). Fluorescence correlation spectroscopy measurements, which essentially measure the cytoplasmic diffusion coefficient and should not be expected to be affected by membrane furrows, have suggested a high cytoplasmic diffusion coefficient for Bicoid (16). Our multiscale modeling provides an explanation for the discrepancy between the physiological diffusion coefficient of Bicoid measured by these different techniques.…”
Section: Discussionmentioning
confidence: 83%
“…Quantitative assessment of the actual diffusion coefficient of Bicoid has remained controversial, with some recent estimates differing by several orders of magnitude (5,(15)(16)(17). Previous FRAP experiments have suggested that the diffusion coefficient is too small for the simple SDD model to explain the Bicoid gradient (15).…”
Section: Discussionmentioning
confidence: 99%